Task Taxonomy for Graph Visualization - Lee, Bongshin; Plaisant, Catherine; Parr, Cynthia Sims; Fekete, Jean-Daniel; Henry Riche, Nathalie (In Proceedings of the 2006 AVI workshop on BEyond time and errors: novel evaluation methods for information visualization, 2006)
Our goal is to define a list of tasks for graph visualization that has enough detail and specificity to be useful to: 1) designers who want to improve their system and 2) to evaluators who want to compare graph visualization systems. In this paper, we suggest a list of tasks we believe are commonly encountered while analyzing graph data. We define graph specific objects and demonstrate how all complex tasks could be seen as a series of low-level tasks performed on those objects. We believe that our taxonomy, associated with benchmark datasets and specific tasks, would help evaluators generalize results collected through a series of controlled experiments.